Cold ion chemistry within Coulomb crystals - Heazlewood, B (Taylor and Francis, 2019)
Coulomb crystals are ordered structures of spatially-localised ions, held within an ion trap and exhibiting very low translational temperatures. The many advantages of studying the spectroscopic, kinetic and dynamic properties of gas phase ions in Coulomb crystals – such as the ability to manipulate and detect single ions under ultrahigh vacuum conditions – have seen their adoption in an ever-expanding range of fields. This article provides an overview of recent developments, where Coulomb crystals have been utilised for precision measurements, for the study of controlled ion-neutral reactions and in the implementation of quantum information science .